Actantial variation in Santiago del Estero Quichua: the applicatives (Part II) - Albarracín, Lelia Inés (2022)
The dialectal variety of Quechua spoken in the province of Santiago del Estero, Argentina, has basically two mechanisms that allow the increase of verbal valency: through causatives or applicatives. In a previous article we have described the mechanisms of increasing verbal valency through applicatives in the case of intransitive verbs. In this paper we return to this issue, extending the analysis for unitransitive and ditransitive verbs by means of examples with verbs of different valency structure. We have also considered cases of combinations between applicatives, their restrictions and the different interpretations that arise according to the context. The results obtained allowed us to determine the limits that verbal valences impose on the behavior of the different types of applicatives.